Activated carbon@SAPO-11 / kaolin composite acidic material and preparation method thereof
The activated carbon@SAPO-11/kaolin composite material addresses the limitations of traditional molecular sieves by using kaolin and phosphoric acid to create a mesoporous structure with adjustable ratios, improving macromolecular catalysis applicability and reducing environmental and economic burdens.
Patent Information
- Application Number
- CN202310321928.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-29
AI Technical Summary
Existing molecular sieves with narrow pore structures and the use of organic templates in their preparation pose limitations for macromolecular catalysis, leading to environmental pollution and high costs, while conventional methods for synthesizing stepped pore molecular sieves face challenges with large template agent consumption and difficult control of mesoporous ratios.
A composite acidic material is prepared using activated carbon@SAPO-11/kaolin, where kaolin is activated and dealuminated, combined with phosphoric acid, and subjected to crystallization and carbonization to create a mesoporous structure with adjustable proportions, eliminating the need for organic templates.
The resulting material provides a microporous structure from SAPO-11 and mesoporous structure from activated carbon and kaolin, allowing flexible adjustment of mesoporous ratios, enhancing its applicability in macromolecular catalysis and reducing environmental impact and costs.
Smart Images

Figure CN116273153B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic materials, and specifically relates to an activated carbon@SAPO-11 / kaolin composite acidic carrier material and a preparation method thereof. Background Art
[0002] Acid-catalyzed reaction, as one of the important reactions in the field of chemistry and chemical industry, is widely used in the fields of petrochemical industry, medicine, food, environmental protection and bioengineering. Therefore, the development of acidic materials is one of the important research topics in the field of catalysis. Molecular sieves are a type of microporous acidic materials connected by Si and Al atoms through oxygen bridges. Due to their regular pore structure and adjustable surface acidity, they have become an indispensable catalytic material for petroleum processing and fine chemicals. To date, there are more than 120 types of molecular sieves. However, the narrow pore structure of microporous molecular sieves limits their application in the field of macromolecular catalysis. For this reason, stepped pore molecular sieves with a certain mesoporous structure have been widely studied in order to obtain a molecular sieve acidic material with lower mass transfer resistance that can be used for macromolecular catalysis, thereby broadening the application of molecular sieves in the field of macromolecular catalysis.
[0003] The pore structure of commercial micro-mesoporous SAPO-11 molecular sieve materials is not adjustable, and organic mesoporous templates are mostly used in their preparation. The use of organic templates not only pollutes the environment, but also increases costs. Invention patent ZL 202110962680.5 discloses a method for preparing step-pore molecular sieves using natural clay. First, natural clay is calcined at high temperature and then alkali solution is added to extract part of the Si element to obtain clay ore with low silicon content and silicate alkali solution. The obtained clay ore with low silicon content is used to synthesize Fe-SAPO molecular sieves, and the silicate alkali solution is used to synthesize step-pore MFI, MOR or TS-1. A green synthesis route for molecular sieves is obtained, which solves the problem that step-pore molecular sieves need to add mesoporous templates. Invention patent ZL202110735921.2 discloses a method for synthesizing step-pore SAPO-11 molecular sieves based on natural mineral green, which dissolves kaolin in hydrochloric acid solution after high-temperature roasting, and then adds aluminum element and template agent, and crystallizes to obtain the final product. The synthesized SAPO-11 molecular sieve has the characteristics of high crystallinity, large external specific surface area and no need for mesoporous template agent. Invention patent ZL 202111533953.0 discloses a method for synthesizing a large unit cell parameter mesoporous molecular sieve, which uses a non-ionic surfactant and an anionic auxiliary template agent and adds cellulose ether. The liquid crystal structure formed by cellulose ether in water restricts the silicon source and aluminum source, thereby obtaining a mesoporous molecular sieve with a larger unit cell parameter. The synthesis of the above-mentioned step-pore molecular sieve has the disadvantages of large amount of template agent and difficult control of mesoporous ratio, which is not conducive to industrial production. Summary of the invention
[0004] The purpose of the present invention is to provide an activated carbon @ SAPO-11 / kaolin composite acidic carrier material and a preparation method thereof, which uses natural kaolin as a raw material, and finally obtains a composite acidic material with a stepped pore structure by subjecting kaolin to high-temperature activation, phosphoric acid "dealuminization", crystallization and high-temperature carbonization. The composite acidic material has the advantages of a mesoporous structure and adjustable proportions.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] An activated carbon@SAPO-11 / kaolin composite acidic material, the preparation method of which comprises the following steps:
[0007] (1) calcining kaolin at a certain temperature to obtain metakaolin, then adding a phosphoric acid solution of a certain concentration, and conducting a water bath at a certain temperature to obtain a dealuminated kaolin acid solution;
[0008] (2) taking the above kaolin acid solution, adding deionized water, silicon source, aluminum source and template agent in sequence and stirring evenly, placing the obtained mixed solution in a ball mill for ball milling, transferring it to a stainless steel reactor with a polytetrafluoroethylene liner, performing hydrothermal crystallization in a homogeneous reactor, and then cooling, centrifuging and washing to obtain a SAPO-11 / kaolin intermediate product;
[0009] (3) mechanically stirring a certain amount of high molecular weight polymer and the SAPO-11 / kaolin intermediate product obtained above, and then heating at a certain temperature until a gel structure is formed, thereby obtaining a high molecular weight gel containing SAPO-11 / kaolin;
[0010] (4) The polymer gel containing SAPO-11 / kaolin obtained above is carbonized at a certain temperature to obtain an activated carbon@SAPO-11 / kaolin composite acidic material with stepped pores.
[0011] Furthermore, the concentration of the phosphoric acid solution in step (1) is 1-4 mol / L, and the amount thereof added is 5 mL per gram of kaolin.
[0012] Furthermore, the calcination temperature is 600-1000°C, and the calcination time is 4-6 h; the water bath temperature is 50-90°C, and the calcination time is 1-2 h.
[0013] Furthermore, the amount of aluminum source added in step (2) is converted according to the molar ratio of phosphorus to aluminum in the obtained mixed solution of 0.7-1.5:1; the amount of silicon source added is converted according to the molar ratio of silicon to aluminum in the obtained mixed solution of 0.3-0.5:1; the molar ratio of the amount of the template to the aluminum in the mixed solution is 0.4-1.5:1, and the amount of deionized water added is converted according to the molar ratio of water to aluminum in the obtained mixed solution of 30-120:1.
[0014] The silicon source includes one or more of metakaolin, tetraethyl orthosilicate, silica sol and white carbon black; the aluminum source includes one or more of metakaolin, pseudo-boehmite and aluminum isopropoxide; and the template includes one or more of di-n-propylamine, diisopropylamine and di-n-butylamine.
[0015] Furthermore, in step (2), the rotation speed of the ball mill is 1000-15000 r / min, and the time is 1-2 h; the temperature of the hydrothermal crystallization is 140-200°C, the rotation speed is 50-480 r / min, and the time is 2-72 h.
[0016] Furthermore, the mass ratio of the high molecular polymer used in step (3) to the intermediate product of SAPO-11+kaolin is 0.5-1.5:1; the high molecular polymer comprises one or more of starch and cellulose. Among them, starch can be one or more of corn starch, sweet potato starch, potato starch, wheat starch and pea starch. Cellulose can be one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose.
[0017] Furthermore, the heating temperature in step (3) is 150-200°C.
[0018] Furthermore, the carbonization temperature in step (4) is 500-800°C and the time is 3-4 h.
[0019] The consumption of template agent is large and the mesoporous ratio is difficult to control in the preparation process of conventional step-pore molecular sieves. The present invention provides a method for preparing a step-pore acidic carrier material with a mesoporous structure and an adjustable ratio. The preparation process uses activated and dealuminated kaolin and phosphoric acid solution as silicon source and phosphorus source, respectively, which provide raw materials and mesoporous structure for the formation of SAPO-11 molecular sieves. In addition, the SAPO-11 / kaolin polymer gel is carbonized to produce a mesoporous structure. The mesoporous structure can also be flexibly adjusted through the dealumination and carbonization process of kaolin.
[0020] Compared with the existing graded pore molecular sieves, the advantages of the present invention are: the synthesized activated carbon @ SAPO-11 / kaolin composite acidic material, the micropores are mainly provided by SAPO-11, the mesopores are provided by activated carbon and kaolin, and the mesoporous structure can be flexibly adjusted through the kaolin dealumination and carbonization process. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The XRD spectra of the materials obtained in Examples 1-4 and Comparative Example 1 are as follows;
[0022] Figure 2 N2 adsorption-desorption isotherms of the materials obtained in Examples 1-4 and Comparative Example 1;
[0023] Figure 3 The pore size distribution diagram of the materials obtained in Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION
[0024] An activated carbon@SAPO-11 / kaolin composite acidic material, the preparation method of which comprises the following steps:
[0025] (1) Calcinate kaolin at 600-1000 °C for 4-6 h to obtain metakaolin, then add 1-4 mol / L phosphoric acid solution at a rate of 5 mL / g, and place in a water bath at 50-90 °C for 1-2 h to obtain a dealuminated kaolin acid solution;
[0026] (2) Take the above kaolin acid solution, add deionized water, silicon source, aluminum source and template agent in sequence and stir evenly, put the obtained mixed solution into a ball mill, and after ball milling at 1000-15000 r / min for 1-2 h, transfer it to a stainless steel reactor with a polytetrafluoroethylene liner, and hydrothermally crystallize it at 140-200 ° C in a homogeneous reactor at a speed of 50-480 r / min for 2-72 h, and then cool, centrifuge and wash to obtain a SAPO-11 / kaolin intermediate product;
[0027] (3) mixing the polymer and the SAPO-11 / kaolin intermediate product obtained above at a mass ratio of 0.5-1.5:1, mechanically stirring, and then heating at 150-200° C. until a gel structure is formed, thereby obtaining a polymer gel containing SAPO-11 / kaolin;
[0028] (4) The obtained polymer gel containing SAPO-11 / kaolin is carbonized at 500-800 °C under nitrogen or argon purge conditions for 3-4 h to obtain an activated carbon@SAPO-11 / kaolin composite acidic material with stepped pores.
[0029] The amount of aluminum source added in step (2) is converted according to the molar ratio of phosphorus to aluminum in the obtained mixed solution of 0.7-1.5:1; the amount of silicon source added is converted according to the molar ratio of silicon to aluminum in the obtained mixed solution of 0.3-0.5:1; the molar ratio of the amount of the template to the aluminum in the mixed solution is 0.4-1.5:1, and the amount of deionized water added is converted according to the molar ratio of water to aluminum in the obtained mixed solution of 30-120:1.
[0030] The silicon source includes one or more of metakaolin, tetraethyl orthosilicate, silica sol and white carbon black; the aluminum source includes one or more of metakaolin, pseudo-boehmite and aluminum isopropoxide; and the template includes one or more of di-n-propylamine, diisopropylamine and di-n-butylamine.
[0031] The high molecular polymer in step (3) includes one or more of starch and cellulose. The starch may be one or more of corn starch, sweet potato starch, potato starch, wheat starch and pea starch. The cellulose may be one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose.
[0032] In order to solve the limiting effect of the pores of traditional microporous molecular sieve carriers and the problems of large dosage and high cost of commercial template agents, the present invention uses natural kaolin as raw material and utilizes the pore structure of kaolin to prepare a carrier material with a stepped pore structure and an adjustable micro-mesoporous ratio, so as to improve the connectivity of the pores of the acidic carrier material and provide a new idea for the development of ideal pore materials required for the preparation of natural minerals.
[0033] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0034] Example 1
[0035] (1) Activation and dealumination of kaolin: calcining kaolin at 850 °C for 4 h to obtain metakaolin, then adding 4 mol / L phosphoric acid solution at a concentration of 5 mL / g under stirring conditions, and treating in a 70 °C water bath for 1 h to obtain a dealumination-activated kaolin acid solution;
[0036] (2) Synthesis of SAPO-11 / kaolin intermediate: 12.8 g of the dealuminated activated kaolin acid solution obtained in step (1) was weighed, and 28.31 g of water, 2.28 g of pseudo-boehmite, 1.26 g of tetraethyl orthosilicate, and 3.06 g of di-n-propylamine were added in sequence under stirring to form a gel precursor, wherein the molar ratio of the precursor is: 1Al2O3:0.9P2O5:0.3SiO2:1.5DPA:100H2O; the precursor was then added to a ball mill and ball-milled at 12000 r / min for 30 min, and finally transferred to a stainless steel reactor with a polytetrafluoroethylene liner, and crystallized in a homogeneous reactor at 180°C and 480 r / min for 24 h, and then cooled, centrifuged, and washed to obtain a SAPO-11 / kaolin intermediate;
[0037] (3) Preparation of SAPO-11 / kaolin polymer gel: Add 70 g of deionized water to 6 g of the SAPO-11 / kaolin intermediate product obtained in step (2) and stir evenly, then add 5 g of carboxymethyl cellulose and 3 g of corn starch and stir evenly, and heat at 160 °C until a gel structure is formed to obtain a SAPO-11 / kaolin polymer gel;
[0038] (4) Preparation of activated carbon @ SAPO-11 / kaolin composite material: The polymer gel containing SAPO-11 / kaolin obtained in step (3) was carbonized at 600 °C under nitrogen purge for 3 h to obtain an activated carbon @ SAPO-11 / kaolin composite acidic material, named C-1.
[0039] Example 2
[0040] In step (3), no carboxymethyl cellulose was added, and the amount of corn starch added was increased from 3 g to 6 g. Other operations were the same as in Example 1. The obtained material was named C-2.
[0041] Example 3
[0042] The crystallization temperature in step (2) was adjusted to 170 °C and the crystallization time was adjusted to 48 h. Other operations were the same as in Example 1. The obtained material was named C-3.
[0043] Example 4
[0044] The molar ratio of the gel components in step (2) is adjusted to: 1Al2O3:1.2P2O5:0.3SiO2:1.5DPA:100H2O. That is, 14.4 g of the dealuminated kaolin acid solution obtained in step (1) is weighed, and 27.35 g of water, 1.94 g of pseudo-boehmite, 1.26 g of tetraethyl orthosilicate, and 3.06 g of di-n-propylamine are added in sequence under stirring to form a precursor. The crystallization time and crystallization temperature in Example 3 are used, and other operations are the same as in Example 1. The obtained material is named C-4.
[0045] Comparative Example
[0046] The SAPO-11 purchased from Nankai University was used as a comparative sample, with a crystallinity of 100 and named D-1.
[0047] The results of the physical properties of the obtained materials are shown in Figure 1-3 And Table 1.
[0048] Table 1 Product physical properties
[0049]
[0050] Depend on Figure 1 It can be seen that the materials prepared in Examples 1-4 all have an AEL topological structure, and their relative crystallinity are 64%, 67%, 84% and 91%, respectively, indicating that the synthesized products are all activated carbon@SAPO-11 / kaolin composite acidic materials, among which the composite material obtained in Example 4 has a higher content of SAPO-11.
[0051] And by Figure 2It can be seen that all the materials used have micro-mesoporous structures and belong to step-pore materials. And from Table 1, we can see that the specific surface area of C-1 is 217 m 2 / g, and the mesopore volume is 0.23 m 2 / g, the specific surface area of C-2 is 214 m 2 / g, mesopore volume is 0.23m 2 / g, the specific surface area of C-3 is 150 m 2 / g, and the mesopore volume is 0.15 m 2 / g, the specific surface area of C-4 is 145 m 2 / g, and the mesopore volume is 0.07 m 2 / g, while the specific surface area of D-1 is 125 m 2 / g, and the mesopore volume is 0.21 m 2 / g.
[0052] Depend on Figure 3 It can be seen that compared with C-1, when carboxymethyl cellulose is not added to the synthesis system and the amount of corn starch added is increased, the pore structure performance of the obtained material C-2 does not change much; when the crystallization temperature of the synthesis system is adjusted to 170 ℃ and the crystallization time is adjusted to 48 h, the content of SAPO-11 molecular sieve in the obtained material C-3 increases, resulting in a decrease in the number of large mesopores of kaolin, which is consistent with the results in Table 1; when the molar ratio of the gel component in the synthesis system is adjusted to 1Al2O3:1.2P2O5:0.3SiO2:1.5DPA:100H2O, the content of SAPO-11 molecular sieve in the obtained material C-4 is further increased, and the number of large mesopores of kaolin is further reduced.
[0053] The above analysis results show that the present invention uses kaolin as raw material to successfully synthesize an activated carbon @SAPO-11 / kaolin composite acidic material with a ladder pore structure, wherein the SAPO-11 molecular sieve provides micropores, and the activated carbon and kaolin provide mesopores. The mesoporous structure and proportion of the activated carbon @SAPO-11 / kaolin composite acidic material can be flexibly adjusted, which provides a new way for the development of macromolecular catalyst acidic materials.
[0054] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing an activated carbon@SAPO-11 / kaolin composite acidic material, characterized in that: The following steps are involved: (1) calcining kaolin at a certain temperature to obtain metakaolin, then adding a phosphoric acid solution of a certain concentration, and conducting a water bath at a certain temperature to obtain a dealuminated kaolin acid solution; (2) taking a kaolin acid solution, adding deionized water, a silicon source, an aluminum source and a template agent in sequence and stirring evenly, transferring the obtained mixed solution to a stainless steel reactor lined with polytetrafluoroethylene after ball milling, performing hydrothermal crystallization in a homogeneous reactor, and then cooling, centrifuging and washing to obtain a SAPO-11 / kaolin intermediate product; (3) mechanically stirring a certain amount of high molecular weight polymer and the obtained SAPO-11 / kaolin intermediate product, and then heating them at a certain temperature until a gel structure is formed, thereby obtaining a high molecular weight gel containing SAPO-11 / kaolin; (4) carbonizing the obtained polymer gel containing SAPO-11 / kaolin at a certain temperature to obtain an activated carbon@SAPO-11 / kaolin composite acidic material with stepped pores; The mass ratio of the high molecular polymer used in step (3) to the intermediate product of SAPO-11 / kaolin is 0.5-1.5:1; the high molecular polymer includes one or more of starch and cellulose; and the heating temperature is 150-200°C.
2. The method for preparing the activated carbon@SAPO-11 / kaolin composite acidic material according to claim 1, characterized in that: The concentration of the phosphoric acid solution in step (1) is 1-4 mol / L, and the amount added is 5 mL per gram of kaolin.
3. The method for preparing the activated carbon@SAPO-11 / kaolin composite acidic material according to claim 1, characterized in that: The calcination temperature in step (1) is 600-1000°C for 4-6 h; the calcination temperature in the water bath is 50-90°C for 1-2 h.
4. The method for preparing the activated carbon@SAPO-11 / kaolin composite acidic material according to claim 1, characterized in that: The amount of aluminum source added in step (2) is converted according to the molar ratio of phosphorus to aluminum in the obtained mixed solution of 0.7-1.5:1; the amount of silicon source added is converted according to the molar ratio of silicon to aluminum in the obtained mixed solution of 0.3-0.5:1; the molar ratio of the amount of the template to the aluminum in the mixed solution is 0.4-1.5:1, and the amount of deionized water added is converted according to the molar ratio of water to aluminum in the obtained mixed solution of 30-120:
1.
5. The method for preparing the activated carbon@SAPO-11 / kaolin composite acidic material according to claim 1 or 4, characterized in that: The silicon source includes one or more of metakaolin, tetraethyl orthosilicate, silica sol and white carbon black; the aluminum source includes one or more of metakaolin, pseudo-boehmite and aluminum isopropoxide; and the template includes one or more of di-n-propylamine, diisopropylamine and di-n-butylamine.
6. The method for preparing the activated carbon@SAPO-11 / kaolin composite acidic material according to claim 1, characterized in that: The ball milling speed in step (2) is 1000-15000 r / min, and the time is 1-2 h; the hydrothermal crystallization temperature is 140-200 °C, the speed is 50-480 r / min, and the time is 2-72 h.
7. The method for preparing the activated carbon@SAPO-11 / kaolin composite acidic material according to claim 1, characterized in that: The carbonization temperature in step (4) is 500-800°C and the time is 3-4 h.
